Evaluation of the effect of integrated fertilization on some soil properties and the growth and yield of Armenian cucumber (Cucumis melo var.flexuosus Nauds) - Kadhimiyah (University of Thi-Qar Journal of agricultural research, 2023)
This study aimed to evaluate the effect of integrated fertilization (chemical, organic, and biological) on some chemical and biological properties of soil as well as the growth and yield of Armenian cucumber (Cucumis melo var. flexuosus). A field experiment was carried out with five fertilizer treatments (control without fertilizer, chemical fertilizer (CF), organic fertilizer (OF), biological fertilizer (BF) and their mixture (CF+OF+BF). The following properties were evaluated: soil salinity (EC), soil reaction (pH), organic matter content (OM), NPK concentration in soil and plant, and numbers of Azotobacter and Pseudomonas bacteria in the rhizosphere. The results showed that the integrated fertilization treatment was superior in improving the chemical properties of the soil, as it reduced the EC and pH values, and increased OM. It also recorded the highest concentrations of major nutrients in the soil and plant (N: 40,000, P: 44,000, K: 40,000 mg kg⁻¹), compared to the control treatment. It led to a significant increase in the numbers of beneficial bacteria 28.66×10³ and 23.33×10³ cfu /g soil for Azotobacter and Pseudomonas, respectively. These results confirm the effectiveness of integrated fertilization in enhancing soil fertility and improving nutritional and biological efficiency, which supports its adoption as a sustainable strategy as an alternative or complement to traditional chemical fertilization.